(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Candida glabrata infections being resistant to many azole antifungal agents, are difficult to treat. Various parts of Adenanthera pavonina have been used in traditional medicine. In the present study, an attempt was made to screen the bioefficacy of the identified phytoconstituents of A. pavonina on an in silico platform and identify some potential drug-like molecules that can impede important drug targets of C. glabrata using the molecular docking method. In a previous study related to the current research, the phytochemical profiling of the methanolic stem extract of A. pavonina was carried out using GC-MS to identify the phytoconstituents. The three-dimensional structure of the fungal receptors were derived by homology modeling using Modeller9v7 and the same for the ligands for which the structures were not available were drawn by ACD chemSketch. The docking of ligands and receptors were performed using PatchDock software. Druglikeliness and pharmacodynamics properties were evaluated using SWISS-ADME. GC-MS analysis of the A. pavonina extract revealed the presence of 17 phyto compounds, of which 2 heptyl 1,3dioxolane and methyl 4-o-methyl-d-arabinopyranoside best docked with the epithelial adhesion protein 6 receptor and cell wall transcription factor ACE2. Methyl 4-o-methyl-d-arabinopyranoside also best docked with the integral cell wall protein receptor. Although other compounds have shown good scores related to docking 2 heptyl 1, 3 dioxolane had an excellent binding affinity than the other ligands thus signifying its potent antifungal activity. 2 Heptyl 1, 3 Dioxolane was found to be BBB positive and 4-O-Methyl-D-arabinopyranoside is BBB negative. As the finding indicates, the two phyto compounds present in the methanolic stem extract of A. pavonina demonstrated good docking scores when docked with specific fungal cell wall receptors and thus can prove to be appropriated for the lead molecule.